Exploring Visual Cryptography Techniques: A Comprehensive Review - Alauldeen Al-Bayati, Hajir; M. Jawad, Lahieb; N. Hamod, Dalal (Al-Nahrain Journal of Science, 2024)
The backdrop: visual cryptography represents a contemporary encryption technology valued for its ease of implementation and comprehensibility, eliminating the need for a secure channel for key transmission and similar requirements. This paper aims: delve into the diverse methods employed in optical encryption, exploring their advantages and drawbacks, with a particular focus on image encryption techniques and the outcomes documented in various research studies. The objective is to identify the strengths and weaknesses inherent in these methodologies, paving the way for potential solutions in the future of optical encryption research. Notably, challenges persist in effectively handling color images and utilizing multiple shares (n, n), impacting both the security and the restoration aspects. The time computation aspects, encompassing creation, encryption, and restoration of these shares, also present challenges. Consequently, ongoing improvements are necessary to address these intricacies and enhance the robustness and applicability of visual cryptography technologies in diverse contexts.